Minimally Invasive Approach in Surgical Management of Renal Neoplasms National Cancer Institute Experience - Selim, Amr Mounir; Zaghloul, Ashraf Saad; AbouLkassem, Hatem Ahmed; Fergany, Amr Farouk; Abdelmaksoud, Abdelmaksoud Mohamed; Fadlalla, Waleed Mohamed; Elhakim, Mahmoud Amr Abd; Allam, Rasha Mahmoud (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Minimally invasive nephrectomy is considered a technically challenging procedure requiring a long learning curve to reach acceptable warm ischemia time and perioperative complications. These minimally invasive techniques result in a shorter hospital stay and less post-operative pain. AIM: This study aims to demonstrate the National Cancer Institute experience regarding the benefits of laparoscopic and robot-assisted nephrectomy over open technique. METHODS: This is a retrospective descriptive cohort study including 62 patients with renal masses treated with nephrectomy whether partial, total or radical, 26 cases were treated by minimally invasive techniques (8 robotic and 18 laparoscopic), while 36 cases were treated by open technique. Inclusion criteria were patients between 20 and 70 years with renal neoplasm without renal vein thrombosis, with tumor stage T1 or T2 N0 M0. Exclusion criteria were patients with medical comorbidities that preclude surgical management or minimally invasive techniques and patients refusing surgery in general. RESULTS: Minimally invasive nephrectomy resulted in shorter hospital stay (mean hospital stay was 2.2 days for the minimally invasive group and 3.6 days for the open group) and less post-operative pain than open technique (p < 0.001 and = 0.002, respectively), while open technique resulted in shorter operation time (p = 0.039, mean operation time 147.8 min compared to 184.8 in the minimally invasive group). CONCLUSION: Minimally invasive nephrectomy (laparoscopic and robotic) resulted in less post-operative pain and shorter hospital stay compared to open technique despite consuming longer operation time which may be decreased by improving the learning curve of operating surgeons.